Self-help groups revolution: what next? - Jairam Ramesh (2007)
Self-help groups, the major form of delivery of microfinance in India, have brought about dramatic changes in the lives of lakhs of women. In Andhra Pradesh, which has the largest network of SHGs and where the government has been a strong supporter, they have gone beyond provision of credit and assumed many non-traditional responsibilities. The Andhra model is one that other states should consider replicating. - Reproduced.
Keywords: Self help